2022
DOI: 10.3390/ijerph19031523
|View full text |Cite
|
Sign up to set email alerts
|

Promoting and Risk Factors of Nurses’ Hardiness Levels during the COVID-19 Pandemic: Results from an Italian Cohort

Abstract: Aim: Few studies in the literature specifically address the hardiness of nurses during the COVID-19 pandemic. Thus, the primary aim of this study was to assess the impact of COVID-19 on the hardiness levels in an Italian cohort of nurses. The secondary aims were to assess the level of hardiness in nurses directly caring for patients with COVID-19 and to verify the presence of related risk and promoting factors. Methods: A descriptive and explorative study was performed through an online survey from March to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Resilience in front line healthcare workers has been examined by other investigators. 20 , 21 Authors found that resilience was important in coping and maintaining mental health. In evidence gathered prior to the pandemic, authors indicated that resilience was an adaptive factor for nurses during difficult situations, even transforming challenges into positive experiences and professional growth.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience in front line healthcare workers has been examined by other investigators. 20 , 21 Authors found that resilience was important in coping and maintaining mental health. In evidence gathered prior to the pandemic, authors indicated that resilience was an adaptive factor for nurses during difficult situations, even transforming challenges into positive experiences and professional growth.…”
Section: Discussionmentioning
confidence: 99%
“…During the three years of the pandemic, many studies were prepared to describe the experience of medical personnel in the fight against COVID-19 in various countries and various medical units [19,21]. The results of this ongoing research have shown that working during the pandemic has had a very large impact on the personal and professional lives of nurses, as they are one of the most exposed professional groups due to direct contact with patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the pandemic, despite the scarce existing studies, hardiness has shown a protective role in nurses. Of particular relevance is that anxiety, when associated with a greater length of service, has been found to be a promoting factor for hardiness, showing that anxiety is not always associated with a decrease in hardiness ( Baldassini Rodriguez et al 2022 ). It has been pointed out that the presence, activation and effects of hardiness are not universal, making it of great interest to analyze the variables and processes that influence the mobilization of strengths in the implementation of advanced nursing ( Druart and Blanchard, 2022 ).…”
Section: Introductionmentioning
confidence: 99%